KAJIAN NILAI EKONOMI PENERAPAN KONSEP DAUR ULANG PADA TPA JATIBARANG KOTA SEMARANG - Handayani, Dwi Siwi; Budisulistiorini, Sri Hapsari; Nuraini, Mya Rosie (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2009)
There is no advance structural treatment to the solid waste in Semarang city. The usage of TPA Jatibarang, landfill in Semarang City, has alreadyÂ  exceed its limit. It can threaten the continuity of management of the solid waste in Semarang city. Therefore, the study of landfill management alternative on TPA Jatibarang is needed to longer the usage limit and maintain the operational of solid waste management in TPA Jatibarang, save the landfill area and produce economic value for both the manager and the scavenger. The composition of solid waste in TPA jatibarang are 78% wet garbage and 22% dry garbage, both kind oh garbage can be recycled so it will have high economic value. The recycle concept started with separation, continued with cutting out for each kind of dry garbage and composting for the wet garbage can produce high profit. Until the planning year of 2025, the profit is Rp 1.165.581.879.809,-. The profit not only for the manager but also fir the staff in recycling process. And for the scavenger, their income will increase if they work as the recycling staff. The income raising is from Rp. 19.000,-/person/day into Rp. 35.000,-/person/day will increase the life quality of the scavenger.